Attention as the basic component of cognitive functions of the brain and its features in children with bronchial asthma - S. M. Nedelska; О. Yu. Akulova; Т. Ye. Shumna (Zaporožskij Medicinskij Žurnal)
Purpose. To study the characteristics of attention in children with bronchial asthma (BA) taking into account their sex differences, depending on the course, duration and control of the disease.